PENGARUH PEMANFAATAN ECENG GONDOK (Eichhornia crassipes) FERMENTASI DALAM RANSUM TERHADAP PERFORMANS ITIK LOKAL JANTAN UMUR 2-9 MINGGU - Magdalena Siregar; Chiristine Octavia Banjarnahor (Universitas Pembangunan Panca Budi, 2020)
This study aims to determine the effect of fermented water hyacinth (Eichhornia crassipes)fermentation in the ration against the rate of feed consumption, body weight gain, and feedconvertion of nine week old male local ducks and to study were determined the best level the rate offeed consumption, body weight gain, and feed convertion of nine weeks. The research design uses aCompletely Randomized Design (CRD) with five treatment and each treatment was repeated fourtimes and each repeat consist of five male local ducks. The research showed that water hyacinth(Eichhornia crassipes) fermentation in the ration utilization give unsignificantly (P>0.05) influenceto feed consumption and feed convertion. But give significsntly (P<0.05 )to body weight gain.The bestlevel of the giving of water hyacinth (Eichhornia crassipes) fermentation in the ration found on P3with level15%.——————